Politik Hukum Pengisian Jabatan Publik Melalui Mekanisme Electoral System Oleh Mantan Narapidana - Suparto, Suparto; Muslikhah, Umi (Jurnal Selat, 2020)
The filling of public positions through the electoral system by ex-convicts, especially corruption, raises the pros and cons of the community. This is because corruption belongs to the category of extraordinary crimes (extraordinary crime). KPU as the organizer of the Election issued KPU Regulation No. 20 of 2008 which forbade the nomination of ex-convicts as legislative candidates. However, this regulation is contrary to Article 240 paragraph (1) letter g of the Election Law. This study examines the legal politics of filling public positions through the electoral system mechanism by ex-convicts referring to the decision of the Supreme Court No. 46 P / HUM / 2018 and Constitutional Court Decision No. 42 / PUU-XIII / 2015.